Harmonisasi Aturan Perbukuan dan Hak Cipta sebagai Upaya Mengatasi Pembajakan Buku - Ratih Widowati (Jurnal Hukum Lex Generalis, 2026)
Copyright infringement in the Indonesian book industry continues despite regulations governing it. The legal basis for books is Law No. 3 of 2017 concerning the Book System and Law No. 28 of 2014 concerning Copyright, but these two regulations do not refer to each other. In this study, a normative juridical method was used. The results of the study indicate that this disharmony also contributes to the rampant violation of book copyright. In the digital era, harmonization of regulations is essential to ensure that the law does not lag behind technological progress.